AGE-RELATED CHANGES IN OVARIAN ENDOMETRIOSIS MORPHOLOGY - Sharopov Sayfiddin (Journals Park Publishing, 2024)
Uterine endometriosis is a disease associated with the growth of endometrial tissue in the inner lining of the uterus outside the uterus. This pathology occurs in many women and can seriously affect their reproductive health. The morphologic features of endometriosis include age-related aspects, which affect disease progression, symptomatology, and treatment strategies.
Keywords: Uterine endometriosis, endometrial tissue, morphological changes, immune system, women, diagnosis, doctors.